Understanding barriers and facilitators to implementation of a patient safety bundle for pregnancy-related severe hypertension in 3 North Carolina outpatient clinics: a qualitative study - Aparna G. Kachoria; Hiba Fatima; Alexandra F. Lightfoot; Linda Tawfik; Joan Healy; Asia Carter; Narges Farahi; E. Nicole Teal; Joumana K. Haidar; Herbert B. Peterson; M. Kathryn Menard (Implementation Science Communications)
Abstract Background Pregnancy related hypertension is a leading cause of preventable maternal morbidity and mortality in the US, with consistently higher rates affecting racial minorities. Many complications are preventable with timely treatment, in alignment with the Alliance for Innovation on Maternal Health’s Patient Safety Bundle (“Bundle”). The Bundle has been implemented successfully in inpatient settings, but 30% of preeclampsia-related morbidity occurs in outpatient settings in North Carolina. To address this, we have integrated community engagement and implementation science approaches to identify facilitators and barriers to Bundle implementation, which supports its adaptation for outpatient settings and identifies implementation strategies to be tested in a subsequent study. Methods Eleven key informant interviews were conducted across three clinics to assess the implementation needs for effectively utilizing the Bundle. The interview guide was created using the Consolidated Framework for Implementation Research domains to identify facilitators and barriers to implementation. Additionally, three focus group discussions with patient participants were conducted to understand lived experiences and perceptions of respectful care. A coalition of community partners, patients, providers, those with lived experience, and the research team reviewed materials from the formative study design to dissemination and planning for future study. Results Barriers included inadequate provider-patient interaction time, patients’ lack of transportation to access care, limited protocols to inform/assess/treat/escalate patients, and workforce capacity (staff training and turnover). Facilitators included staff recognition of the importance of treating preeclampsia, champion buy-in of the Bundle’s ability to improve outcomes, co-location of pharmacies for immediate treatment, and staff capacity. Respectful care principles were repeatedly identified as a facilitator for Bundle implementation, specifically for patient awareness of preeclampsia complications and treatment adherence. Conclusions Findings highlight the importance of community-engaged approaches. Further, clinic staff regarded Bundle implementation as crucial for the outpatient setting. Identified barriers suggest that strategies should address systemic social supports (i.e., transportation, childcare) and improve access to and use of home blood pressure monitoring. Identified facilitators support improving communication, increasing clinic champion engagement, enabling systems for identifying at-risk patients, and training staff on accurate blood pressure measurement. Successful Bundle implementation requires addressing systemic barriers to delivering respectful care, such as limited time with patients.